2011
DOI: 10.2118/138521-pa
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Rate Behavior and Imbibition in Shale

Abstract: Summary As part of our investigations of a new chemical imbibition idea (using surfactant or brine formulations) to stimulate oil recovery from shale, we are studying oil flow through and, especially, brine intake into shale to displace oil. Our first studies in this area focused on an outcrop shale, specifically the Odanah member of Pierre shale in North Dakota, USA. We studied porosity, permeability to oil, permeability to water, and spontaneous brine intake for the Pierre shale. We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 5 publications
1
47
1
Order By: Relevance
“…2 and 3, oil-recovery results by use of brine were comparable with those by use of surfactant formulations. This situation was an exception to our previous findings (Wang et al 2012;Zhang et al 2013). We report these results here simply to reveal some of our best imbibition results, and we leave the mechanistic explanation for the results for future papers.…”
Section: Methodscontrasting
confidence: 48%
See 2 more Smart Citations
“…2 and 3, oil-recovery results by use of brine were comparable with those by use of surfactant formulations. This situation was an exception to our previous findings (Wang et al 2012;Zhang et al 2013). We report these results here simply to reveal some of our best imbibition results, and we leave the mechanistic explanation for the results for future papers.…”
Section: Methodscontrasting
confidence: 48%
“…Our previous work (Wang et al 2012) revealed that Bakken cores in their native state are generally oil-wet, with Amott-Harvey indices ranging from -0.150 to -0.810. In this same study, we also demonstrate that the wettability indices fell within a similar range after cleaning (with toluene and methanol) and resaturation with Bakken crude oil.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The literature on shale oil rocks indicates that they are most likely oil-wet (Phillips et al, 2007;Wang et al, 2011;Mirchi et al, 2014). Shuler et al (2011) did some surfactant spontaneous imbibition tests.…”
Section: [11]surfactant Eor In Shale Reservoirsmentioning
confidence: 99%
“…The core slices they used were 1.5 inches in diameter and ½ inches in thickness. Wang et al (2011) also investigated brine imbibition into the outcrop Pierre shale core slices. The core sample thicknesses were 0.65-5 mm.…”
Section: [11]surfactant Eor In Shale Reservoirsmentioning
confidence: 99%